2022
DOI: 10.1186/s12870-022-03848-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiological and coexpression network analyses reveal the potential drought tolerance mechanism of peanut

Abstract: Background Drought stress has negative effects on plant growth and productivity. In this study, a comprehensive analysis of physiological responses and gene expression was performed. The responses and expressions were compared between drought-tolerant (DT) and drought-sensitive (DS) peanut varieties to investigate the regulatory mechanisms and hub genes involved in the impact of drought stress on culture. Results The drought-tolerant variety had ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…These data demonstrate that the enhanced ability to prevent ROS accumulation might contribute to the chilling tolerance of NH5. Our findings are in line with those of previous studies demonstrating that plants with a greater chilling tolerance also exhibit greater antioxidant activity under abiotic stress (Ahmad Lone et al 2022;Ren et al 2022). The ROS induced by chilling stress may act as signalling molecules that trigger defence responses.…”
Section: Discussionsupporting
confidence: 93%
“…These data demonstrate that the enhanced ability to prevent ROS accumulation might contribute to the chilling tolerance of NH5. Our findings are in line with those of previous studies demonstrating that plants with a greater chilling tolerance also exhibit greater antioxidant activity under abiotic stress (Ahmad Lone et al 2022;Ren et al 2022). The ROS induced by chilling stress may act as signalling molecules that trigger defence responses.…”
Section: Discussionsupporting
confidence: 93%
“…Garg et al had constructed several regulatory networks related to chickpea development (Garg et al, 2017). Weighted gene co-expression network analysis (WGCNA) could also offer foundation for the mining of potential hub genes using hierarchical clustering (Ren et al, 2022). These findings demonstrated that the identification of regulatory networks might be effective for precisely understanding transcriptional regulatory mechanisms by using transcriptome analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The JAZ expression was significantly lower in ST than SS in this study, and MYC2 was significantly higher than SS, which may be due to the promotion of the JA hormone transduction pathway (Table S6). JA accumulation is a key metabolite that causes cold and drought resistance in peanuts (Ren et al, 2022; Zhang et al, 2020a), and can enhance the ability of plants to resist adversity (Zhang et al, 2019). The correlation coefficient of LOC112696383 and LOC112790545 encoding the JAZ protein with JA was 0.95.…”
Section: Discussionmentioning
confidence: 99%
“…JA accumulation is a key metabolite that causes cold and drought resistance in peanuts (Ren et al, 2022;Zhang et al, 2020a), and can enhance the ability of plants to resist adversity (Zhang et al, 2019).…”
Section: Ss (10432%mentioning
confidence: 99%